Pengembangan Media Pembelajaran Permainan Edukatif Cari Kata Berbasis Android untuk Menstimulasi Pembelajaran HOTS - Gustina Gustina (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
This research is motivated by the use of learning media for educational games based on android which is still rarely found, even though it is known that 21st-century learning models of learning and learning media are unlimited, and are carried out with the help of information and communication technology. Students are required to think critically, creatively in solving problems in new situations (HOTS). This study aims to produce learning media for android-based educational word search games to stimulate HOTS learning in social studies subjects. This type of research is development research with a 4-D model. This research was conducted at Public Elementary School 54 Payakumbuh with the subject of grade VI students. The results obtained from this study are an educational game looking for words based on android, which can improve student learning outcomes. The results of the validity test of learning media by media experts, material experts, and linguists are very good results. The practicality test of the assessment media was carried out by 25 students, and the assessment by the parents of the students was very good. The test of the effectiveness of learning media shows that student learning outcomes have increased. Based on these results, it was concluded that the learning media for word search educational games were developed and could stimulate HOTS learning.